COVID-19 and Cardiovascular System. Part 3. COVID-19 Current Treatment Approaches: Evidence-Based Review - M. K. Vasilchenko; A. A. Ivannikov; A. N. Yesaulenko; Kh. G. Alidzhanova; S. S. Petrikov (Неотложная медицинская помощь)
Unified management plan and treatment strategy for COVID-19 patients are yet to be discovered. Many trials on COVID-19 interventions have been registered or are ongoing. In this article the results of large-scale clinical trials on COVID-19 treatment are presented, the potential mechanism of action of some drugs is discussed, the features of the main pharmacological and non-pharmacological therapeutic options for COVID-19 patients are described.